Technological Use in EFL Instruction: Investigating Teachers’ Pedagogical Beliefs and Students’ Learning Engagement - Ulfatul Ma'rifah; Nurul Masrifah; Yudhi Arifani (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2021)
This research aimed to find out the influence of EFL teachers’ pedagogical beliefs with regard to using technology on EFL students’ learning engagement in the classroom and also to find out which pedagogical belief dimension most influences EFL students’ learning engagement in the classroom. This is quantitative research with survey method. Data were collected from two online questionnaires. Data analysis methods in this research used descriptive statistics and Structural Equation Modeling (SEM). Respondents in this research were 125 EFL teachers and 125 EFL students in several secondary schools in the second semester of the 2019/2020 academic year in Gresik, East Java, Indonesia. This research found that EFL teachers’ pedagogical beliefs with regard to using technology have a positive and significant influence on EFL students’ learning engagement in the classroom (t-value is 10.840 > 1.96) and the pedagogical belief dimension most influences EFL students’ learning engagement in the classroom is “Teachers’ Practices with Regard to Using Technology” (t-value is 9.953 > 1.96).